Sexual Dimorphism in Mouse Meiosis - Hua, Rong; Liu, Mingxi (Frontiers in Cell and Developmental Biology, 2021)
Meiosis is a highly conserved and essential process in gametogenesis in sexually reproducing organisms. However, there are substantial sex-specific differences within individual species with respect to meiosis-related chromatin reorganization, recombination, and tolerance for meiotic defects. A wide range of murine models have been developed over the past two decades to study the complex regulatory processes governing mammalian meiosis. The present review article thus provides a comprehensive overview of the knockout mice that have been employed to study meiosis, with a particular focus on gene- and gametogenesis-related sexual dimorphism observed in these model animals. In so doing, we aim to provide a firm foundation for the future study of sex-specific differences in meiosis at the molecular level.